Antivenomics and in vivo preclinical efficacy of six Latin American antivenoms towards south-western Colombian Bothrops asper lineage venoms - Mora Obando, Diana (2021)
Snakebite envenoming is an important occupational health problem, particularly in rural areas of developing countries. The timely administration of an effective antivenom remains the mainstay of snakebite management. However, the use of antivenoms is often limited by non-availability due to high cost or by lack of effectiveness. Antivenom shortage can be addressed through the generation of novel polyspecific antivenoms of wide clinical efficacy against the venoms of the medically-relevant snake species within the geographical range where these antivenoms are intended to be deployed, but also by optimizing the paraspecific use of current antivenoms. In Colombia, antivenoms are supplied by two manufacturers, one public, the Instituto Nacional de Salud (INS), and one private, Laboratorios Probiol (PROBIOL). However, the antivenom supply in Colombia has traditionally been insufficient, a circumstance that has led the Colombian Ministerio de Salud y Protección Social to issue several resolutions and decrees to announce this health emergency in the country, and to import antivenoms produced in México and Costa Rica. Contrary to these countries, where B. asper represents the only species of the genus, in SW Colombia three close phylogenetically related B. asper lineages, B. asper (sensu stricto), B. rhombeatus, and B. ayerbei, are responsible for most severe cases of snakebite accidents and exhibit remarkable differences in the physiopathological profile of their envenomings. This work aimed to assess the immunorecognition characteristics of a panel of antivenoms manufactured in Colombia, Costa Rica, Argentina, Perú and Venezuela towards the venoms of the three SW Colombian B. asper lineages. Additionally, combined quantitative in vitro and in vivo data show that the homologous antivenoms produced in Colombia (INS-COL, PROBIOL) and Costa Rica (ICP) effectively neutralize the lethality and the major toxic activities tested of the three SW Colombian B. asper lineage venoms. Heterologous Argentinian (BIOL), Venezuelan (UCV) and Peruvian (INS-PERU) antivenoms also showed comparable, even higher, effective immunocapturing ability towards the venom proteomes of SW Colombian B. asper (sensu stricto), B. rhombeatus, and B. ayerbei, than the Colombian and Costa Rican antivenoms. These results are in line with previous studies highlighting the notable conservation of paraspecific antigenic determinants across the phylogeny of genus Bothrops, and advocate for considering the heterologous Argentinian, Venezuelan and Peruvian antivenoms as further therapeutic alternatives for the treatment of B. asper spp. snakebites in Colombia.